The Drosophila SIFamide Receptor Regulates Sleep and Feeding in a Time-Of-Day Specific Manner. - Velazquez, A.; Cusick, M.R.; De, S.; Beaudouin, A.A.; Stepankovskaya, A.; Tidaback, J.A.; Tsibere, O.; Cavanaugh, D.J. (Genes, Brain, and Behavior, 2025)
To optimize health, organisms must coordinate energy intake and expenditure and apportion related behaviors to appropriate times of day. In the fruit fly, Drosophila melanogaster, the SIFamide (SIFa) neuropeptide impacts multiple behavioral outputs important for energy regulation, including reproductive activity, sleep, and feeding. SIFa-expressing neurons receive convergent inputs from circadian and homeostatic brain regions and extend elaborate projections throughout the central nervous system. Consistent with this distribution pattern, the SIFa receptor (SIFaR) is widely expressed in the brain and ventral nerve cord, providing the anatomical substrate for SIFa signaling to influence a broad range of neuronal functions. To further explore the pleiotropic role of SIFa signaling in behavioral control, we have assessed survival, locomotor activity, sleep, and feeding in SIFaR mutant flies, as well as in flies with RNA interference-induced reduction of SIFaR expression. We find that loss of SIFaR has a complex effect on fly survival that is background- and allele-specific. However, outcrossed SIFaR mutant flies are viable, enabling monitoring of adult behavior. These flies exhibit elevated locomotor activity, reduced sleep, and increased feeding at specific times of day. We also find that SIFaR mutations drastically decrease starvation resistance. These results suggest a prominent role for SIFaR in integrating homeostatic and circadian information to coordinate the magnitude and timing of energy balance-related behaviors.